Exercise as a therapeutic intervention for people with cystic fibrosis. (4th May 2019) - Ward, Nathan; Stiller, Kathy; Holland, Anne E
ABSTRACT: Introduction : The complex multisystem nature of cystic fibrosis (CF) commonly results in reduced exercise tolerance, which is independently associated with poor clinical outcomes. Exercise is routinely recommended as part of the therapeutic regimen in CF to improve both respiratory and non-respiratory impairments. Areas covered : This article summarises the most recent evidence regarding the use of exercise as a therapeutic intervention in CF and discusses some of the practical considerations for exercise prescription in this setting. Clinical trials in progress and future research priorities are outlined. Expert opinion : On the balance of available evidence, exercise is likely to assist in improving physical fitness and health-related quality of life (HRQOL) and may be associated with a slower rate of decline in respiratory function in CF. Limitations to current studies include small sample sizes, study durations insufficient to achieve a training effect and difficulty distinguishing the effects of exercise training from that of other interventions implemented as part of a package of care. Larger, multi-centred trials are required to clarify the role of exercise in CF in improving physical fitness, respiratory function, HRQOL, as a substitute for traditional airway clearance techniques and in the management of common CF-related comorbidities.